Hubungan jerebu dengan kes asma: Kajian di beberapa buah hospital di Lembah Klang - Ismail, Hamidi; Syed Hussain, Tuan Pah Rokiah (Universiti Kebangsaan Malaysia, 2001)
The 1997 haze has led to several health problems. Haze or small particles in the air may cause respiratory diseases such as asthma. Incidently, the member of asthma cases has elevated between August-October 1997. This study was carried out in three hospitals i.e. Hospital Tengku Ampuan Rahimah Kang (HTARK), Hospital Universiti (HU) and Hospital Kuala Lumpur (HKL) to look at the trend in the increase number of asthma cases, based on patients' ages, using Air Pollution Index (API) for the months which showed high concentration of haze component. The data obtained for this study were analysed using qualitative technique. The result of this study indicated a clear pattern or relationship between the haze concentration readings and the number of asthma cases admitted into the three hospitals.